Glyphosate treatment mediates the accumulation of small discrete 5′ and 3′-terminal fragments of 18S rRNA in plant cells - A. V. Zhigailov; A. S. Nizkorodova; K. O. Sharipov; N. S. Polimbetova; B. K. Iskakov (Вавиловский журнал генетики и селекции)
Under many kinds of stress, eukaryotic cells rapidly decrease the overall translation level of the majority of mRNAs. However, some molecular mechanisms of protein synthesis inhibition like phosphorylation of eukaryotic elongation factor 2 (eEF2), which are known to be functional in animals and yeast, are not implemented in plants. We suggest that there is an alternative mechanism for the inhibition of protein synthesis in plant cells and possibly, in other eukaryotes, which is based on the discrete fragmentation of 18S rRNA molecules within small ribosomal subunits. We identified four stressinduced small RNAs, which are 5’and 3’-terminal fragments of 18S rRNA. In the present work, we studied the induction of 18S rRNA discrete fragmentation and phosphorylation of the α-subunit of eukaryotic initiation factor 2 (eIF2α) in germinated wheat embryos in the presence of glyphosate, which imitates the condition of amino acid starvation. Using northern and western blotting, we have shown that stress-induced 18S rRNA fragments started to accumulate in wheat embryos at glyphosate concentrations that did not evoke eIF2α phosphorylation. It was also found that cleavage of 18S rRNA near the 5’-terminus began much earlier than eIF2α phosphorylation, which became noticeable only at higher concentration (500 μM) of glyphosate. This result suggests that discrete fragmentation of 18S rRNA may constitute a regulatory mechanism of mRNA translation in response to stress and may occur in plant cells in parallel with and independently of eIF2α phosphorylation. The identified small 5’and 3’-terminal fragments of 18S rRNA that accumulate during various stresses may serve as stress resistance markers in the breeding of economically important plant crops.